Модель когнитивного пространства системы Guide Bot Topology - Добронравин, Ю.В.; Чугунова, Є.М. (Моделювання та інформаційні технології, 2011)
Results of two experiments intended to discover implicit regularities in the way of human interpretation of spacial information are used as base to develop models for navigation in complex environment of virtual reality agents.